2014
DOI: 10.1111/cen.12524
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidative stress and platelet activation in patients with Cushing's syndrome

Abstract: Summary Objective Cushing Syndrome (CS) is implicated by increased cardiovascular risk (CVR) leading to increased morbidity and mortality. Oxidative stress (OS) and platelet activation (PA) are associated with increased CVR. However, scarce data of OS in CS exist. Our objective was to determine the oxidant–antioxidant balance in CS. Design Fourteen patients with CS at diagnosis and fourteen healthy subjects (NS) were evaluated OS by measuring plasma 15‐F2t‐Isoprostane (15‐F2t‐IsoP), PA by thromboxaneB2 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Moreover, reactive oxygen species frequently observed in impaired and chronic wounds have increasingly been shown to be major players in the activation of platelets and to cause thrombus formation. 37,38 In conclusion, this work shows a novel function for TNFSF14/LIGHT during wound healing; in the absence of this molecule from the cell surface, platelets show higher levels of aggregation, potentially contributing to rapid thrombosis during the early stages of healing, which might contribute to impaired healing by reducing the ability of the blood vessels to transport nutrients and oxygen as well as other serum molecules needed for proper healing of the wound tissue. Furthermore, this environment can lead to cell death, contributing to impaired healing.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, reactive oxygen species frequently observed in impaired and chronic wounds have increasingly been shown to be major players in the activation of platelets and to cause thrombus formation. 37,38 In conclusion, this work shows a novel function for TNFSF14/LIGHT during wound healing; in the absence of this molecule from the cell surface, platelets show higher levels of aggregation, potentially contributing to rapid thrombosis during the early stages of healing, which might contribute to impaired healing by reducing the ability of the blood vessels to transport nutrients and oxygen as well as other serum molecules needed for proper healing of the wound tissue. Furthermore, this environment can lead to cell death, contributing to impaired healing.…”
Section: Discussionmentioning
confidence: 80%
“…By contrast, in 2014, Karamouzis et al (21) described enhanced platelet aggregation in patients with CS: thromboxane A2 (TXA2) has been shown to cause platelet release, activation and accumulation and to exert potent vasoconstrictive effects (22); TXB2, which represents a reliable indicator of TXA2 biosynthesis, was significantly higher (P!0.01) in patients affected by CS (21). It therefore seems likely that there is a minor, albeit significant, increase in platelet functionality in CS.…”
Section: Platelet Activationmentioning
confidence: 96%
“…A recent study showed that SGK1 expression is stimulated by a wide variety of hormones, including GCs and mineralocorticoids (20). A previous systematic review failed to show significantly altered platelet aggregation in patients with CS, although the studies reviewed were of low quality (21).…”
Section: Platelet Activationmentioning
confidence: 99%
“…Vitamin E levels, a suggested marker of the antioxidant status, were significantly lower in CS patients compared to controls. These findings would suggest that excess GCs induce pro-oxidative processes which, in combination with the metabolic comorbidities, lead to a vicious loop of worsening oxidant-antioxidant balance and increased cardiovascular morbidity and mortality (170).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%